Pelatihan Publikasi Artikel Ilmiah Melalui Open Journal System (OJS) dan Plagiarism Bagi Komunitas Literasi Guru SMK - Putri, Lusi Dwi; Soehardi, Fitridawati; Dinata, Marta; Dewi, Sri Hartati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Since the Minister of Administrative and Bureaucratic Reform Decree Number 26 of 1989, namely regarding changing teacher positions to functional positions, teachers have been required to develop their careers. This explains that teachers are required to disseminate the results of Classroom Action Research through seminars, publications, or other means so that the research results can be known to the general public. In general, the dissemination of scientific work is carried out online through the Open Journal System system. However, with the increase in information technology, scientific work produced is prone to plagiarism due to the ease of accessing information. Partners are teachers at SMKN 3 Tanjungpinang, Riau Islands Province. Partners have the problem of a lack of knowledge about how to submit articles via the Open Journal System (OJS) system and plagiarism as well as how to check plagiarism in a scientific work. The method used is to provide knowledge about the Open Journal System (OJS) and Anti-Plagiarism systems and training using software or online Anti-Plagiarism checking applications which can be used for free. The results obtained are that partners understand how to use the OJS system, Plagiarism Checker and Turnitin applications, from 25 (twenty five) participants with a 'Very Good' score of 12%, a 'Good' score of 60%, a 'Medium' score of 28% and 'Not Appearing' value is 0%. Other results in the form of teaching materials and articles with draft status to the Community Service Journal will be published in 2024. The conclusion obtained is the increased capacity of partners in using the OJS system and plagiarism check applications.